Long-term investigation of 3D tissue detailed structure and multiparametric vascular network properties using OCT/OCTA for guiding atopic dermatitis theranostics - Fengxian Du; Huiling Wu; Junwei Xue; Shenglan Yao; Ronghui Li; Jinde Zhang; Haitao Wang; Qi Cheng; Fan Zhao; Ying Huang; Zijian Zhou; Feng Liang; et al. (Journal of Translational Medicine)
Abstract Background Rapid, label-free and depth-resolved imaging of atopic dermatitis (AD) at high resolution has long been a challenge due to current dermoscopes are limited by inadequate resolution, sensitivity and the lack of three-dimensional (3D) imaging capability. Methods Herein, we present promising optical coherence tomography (OCT) and OCT angiography (OCTA) collaborative multi-parameter image processing algorithms (OCT/OCTA) that have been developed for long-term, dynamic longitudinal investigation of subtly changes in tissue structure during the dynamic development of AD, especially in the microvascular network. Results The OCT image demonstrated a ‘roller-coaster’ trend in skin thickness throughout the progression of dermatitis, initially exhibiting an increase and subsequently a decrease. Moreover, the OCTA image enabled the discernment of a displacement of the superficial vascular plexus to deeper layers as the severity of AD increased. Furthermore, the results of the quantitative analysis of vascular multiparametric features at different stages, including vessel diameter, length, and density, also demonstrated a positive correlation with the severity of AD. Conclusion Overall, the full-cycle dynamic changes in skin thickness and depth-resolved vascular alterations during the progression of dermatitis can be effectively predicted using OCT/OCTA, which can inform more targeted AD diagnosis and treatment strategies. Furthermore, this method has the potential to assess therapeutic drug efficacy by capturing microvascular and structural responses across different stages of treatment. The presented methods have the potential to provide new insight into the monitoring of long-term vascular and tissue structure responses before and after therapeutic intervention in a range of AD-related skin diseases.